2023
DOI: 10.1080/21655979.2023.2251696
|View full text |Cite
|
Sign up to set email alerts
|

β-catenin inhibitors in cancer therapeutics: intricacies and way forward

Arundhathi Dev,
Meenakshi Vachher,
Chandra Prakash Prasad

Abstract: β-catenin is an evolutionary conserved, quintessential, multifaceted protein that plays vital roles in cellular homeostasis, embryonic development, organogenesis, stem cell maintenance, cell proliferation, migration, differentiation, apoptosis, and pathogenesis of various human diseases including cancer. β-catenin manifests both signaling and adhesive features. It acts as a pivotal player in intracellular signaling as a component of versatile WNT signaling cascade involved in embryonic development, homeostasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 154 publications
0
6
0
Order By: Relevance
“…We have particularly focused on the results showing that sorafenib-resistant PTC was greatly stimulated by calcium, and cancer stemness involved the following signaling pathways (calcium, Notch, Wnt, PPAR, PI3K/Akt, and TGF/SMAD) than sorafenib-sensitive PTC (Figure 1C, top and bottom) in Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis [28][29][30][31][32]. We hypothesized that highly stimulated calcium-related signaling pathways in sorafenib-resistant PTC cells were key players in escaping cytoplasmic calcium mediated apoptosis under severe endoplasmic reticulum (ER) stress conditions via anti-cancer drug-treated conditions [28,29,33,34]. RNA-seq analysis showed that there was a minor distinction between SERCA (ATP2A) isoforms.…”
Section: Yumc-s-p1mentioning
confidence: 99%
“…We have particularly focused on the results showing that sorafenib-resistant PTC was greatly stimulated by calcium, and cancer stemness involved the following signaling pathways (calcium, Notch, Wnt, PPAR, PI3K/Akt, and TGF/SMAD) than sorafenib-sensitive PTC (Figure 1C, top and bottom) in Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis [28][29][30][31][32]. We hypothesized that highly stimulated calcium-related signaling pathways in sorafenib-resistant PTC cells were key players in escaping cytoplasmic calcium mediated apoptosis under severe endoplasmic reticulum (ER) stress conditions via anti-cancer drug-treated conditions [28,29,33,34]. RNA-seq analysis showed that there was a minor distinction between SERCA (ATP2A) isoforms.…”
Section: Yumc-s-p1mentioning
confidence: 99%
“…Additionally, this binding exhibits a relatively substantial binding area and a moderate binding capacity, making it inherently advantageous for the development of inhibitors ( 47 ). CA, a small molecule derived from natural substances, was discovered to exhibit binding affinity towards the H1 helix of β-catenin in close proximity to BCL9 binding site, consequently disrupting the stability of β-catenin and facilitating its oligomerization and subsequent degradation ( 31 , 56 ). This compound emerged as a highly promising therapeutic candidate for impeding the interaction between β-catenin and BCL9.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, the mechanism of inhibition of these compounds is poorly understood, and these compounds contain functional groups like quinones or taxoflavins that are concerning substructures associated with pan assay interference compounds (PAINS). 5 ICG-001 disrupts binding between CTNNB1 and CBP through binding with CBP and are not particularly potent with micromolar potency. 6 Tankyrase inhibitors, such as IWR-1 and XAV939, stabilize axin and the CK1 activator pryivinium to enhance the activity of the destruction complex, but these compounds do not directly interact with CTNNB1.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many efforts have been made to target the Wnt pathway for cancer therapy. PKF115-584 and CGP04090 disrupt interactions between CTNNB1 and TCF. , However, the mechanism of inhibition of these compounds is poorly understood, and these compounds contain functional groups like quinones or taxoflavins that are concerning substructures associated with pan assay interference compounds (PAINS) . ICG-001 disrupts binding between CTNNB1 and CBP through binding with CBP and are not particularly potent with micromolar potency .…”
Section: Introductionmentioning
confidence: 99%